2014
DOI: 10.1111/apm.12235
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor effect of combining metronomic chemotherapy with adoptive cell immunotherapy in nude mice

Abstract: Adoptive cell immunotherapy with cytokine-induced killer cell (CIK cell) represents a promising non-toxic anticancer therapy. However, the clinical efficacy of CIK cells is limited because of abnormal tumor vasculature. Metronomic chemotherapy shows promising anticancer activity by its potential antiangiogenic effect and reduced toxicity. We hypothesized that metronomic chemotherapy with paclitaxel could improve the antitumor effect of adoptive CIK cell immunotherapy. Mice health status was analyzed by measuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…2). Though moderate, the reduction in tumor growth, given similar cellular doses, was consistent with that observed in pre-clinical models of CIK for NSCLC in the absence of additional interventions [2426], but differ from the ability of CAR-T cells to reduce established tumor growth [12, 27].…”
Section: Discussionsupporting
confidence: 66%
“…2). Though moderate, the reduction in tumor growth, given similar cellular doses, was consistent with that observed in pre-clinical models of CIK for NSCLC in the absence of additional interventions [2426], but differ from the ability of CAR-T cells to reduce established tumor growth [12, 27].…”
Section: Discussionsupporting
confidence: 66%
“…Recently, some studies have proven that combination of antiangiogenesis therapy with immunotherapy could have better antitumor effects in lung adenocarcinoma, indicating tumor immunosuppression and angiogenesis might be tightly connected31323334. In conclusion, hypoxia of lung adenocarcinoma cells could induce both tumor immunosuppression and angiogenesis through the up-regulation of CCL28.…”
Section: Discussionmentioning
confidence: 86%
“…Taken together, at least two major roles are played by CCL28 in lung adenocarcinoma, including immunosuppression and pro-angiogenesis (directly and indirectly), both of which are important targets for cancer therapy. Recently, some studies have proven that combination of antiangiogenesis therapy with immunotherapy could have better antitumor effects in lung adenocarcinoma, indicating tumor immunosuppression and angiogenesis might be tightly connected 31 32 33 34 . In conclusion, hypoxia of lung adenocarcinoma cells could induce both tumor immunosuppression and angiogenesis through the up-regulation of CCL28.…”
Section: Discussionmentioning
confidence: 99%
“…In murine models of ovarian cancer under gemcitabine or paclitaxel, it was shown that gemcitabine decreased the number of MDSCs, while paclitaxel did not. 28 …”
Section: Combination Strategies Of Chemotherapy and Immune Checkpointmentioning
confidence: 99%
“…In murine models of ovarian cancer under gemcitabine or paclitaxel, it was shown that gemcitabine decreased the number of MDSCs, while paclitaxel did not. 28 Based on these findings, different clinical trials evaluating the safety and efficacy of platinumbased chemotherapy with immune checkpoint inhibitors have been designed.…”
Section: Combination Strategies Of Chemotherapy and Immune Checkpointmentioning
confidence: 99%